(untitled) (Research, Society and Development, 2022)
The pandemic caused by COVID-19 brought great challenges to higher education institutions, both teachers and students had to quickly adapt to remote classes. Methodologies were developed to improve the interaction of professors with their students, but evaluation processes carried out remotely were often difficult and not very effective. This research sought to assess the perception of medical students about an innovative evaluative experience carried out during the pandemic period. The assessment consisted of a series of questions sent to the student, who, through him, should answer them by recording a video, using the same platform as the remote classes. The analysis included objective and subjective questions that sought to investigate the students’ point of view regarding the method, under various aspects such as communication skills, level of anxiety, quality of the study environment and connectivity. As well, to the comparison with the concepts of assessments from the pre-pandemic period. The results showed that the method was positive when it provides the student with a moment of learning during the assessment. Also observed that there was a good acceptance of the assessment method and students started to prefer it over the use of conventional assessment platforms. It can be concluded that the activity demystifies the punitive character of the assessments as it allows the student to develop a reflection on the knowledge acquired during the course, as well as the gaps found in the teaching and learning process. In addition to improving communication skills so used in medical practice.